2003
DOI: 10.1554/0014-3820(2003)057[0328:tiohac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of History and Contemporary Stream Hydrology on the Evolution of Genetic Diversity Within Species: An Examination of Microsatellite Dna Variation in Bull Trout, Salvelinus Confluentus (Pisces: Salmonidae)

Abstract: An understanding of the relative roles of historical and contemporary factors in structuring genetic variation is a fundamental, but understudied aspect of geographic variation. We examined geographic variation in microsatellite DNA allele frequencies in bull trout (Salvelinus confluentus, Salmonidae) to test hypotheses concerning the relative roles of postglacial dispersal (historical) and current landscape features (contemporary) in structuring genetic variability and population differentiation. Bull trout e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 101 publications
(52 reference statements)
12
101
1
Order By: Relevance
“…Gorges and waterfalls were well known to inhibit gene flow in many fishes and had a substantial effect on their genetic structure (e.g., Currens et al, 1990;Costello et al, 2003;Taylor et al, 2003;Crispo et al, 2006). We also observed that waterfalls restricted upstream gene flow within S. o'connori and increased its genetic divergence.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Gorges and waterfalls were well known to inhibit gene flow in many fishes and had a substantial effect on their genetic structure (e.g., Currens et al, 1990;Costello et al, 2003;Taylor et al, 2003;Crispo et al, 2006). We also observed that waterfalls restricted upstream gene flow within S. o'connori and increased its genetic divergence.…”
Section: Discussionsupporting
confidence: 59%
“…In others, geographic patterns of genetic structure may be more a product of current environments, involving restricted gene flow, demographic processes (e.g., bottlenecks or founder events), or selection (Templeton et al, 1995). Consequently, assessing the relative influence of these historical and contemporary factors on extant genetic structure has clear implications for questions related to evolutionary change and has become an important consideration in terms of conservation (Costello et al, 2003;Crispo et al, 2006;Hubert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that insufficient time had elapsed since the initial colonization of this area to allow detectable differences among watersheds to accrue, but that contemporary factors modulating dispersal were important in shaping relationships among populations at smaller spatial scales, such as within watersheds. In a large-scale study of bull charr, all populations had low genetic variability, which is likely attributable to post-glacial founding events (Costello et al 2003). In addition, peripheral populations, which were colonized more recently, exhibited lower levels of genetic diversity compared to those central to the species' distribution.…”
Section: H I S T O R I C a L F A C T O R S An D C O N N E C T I V I T Ymentioning
confidence: 96%
“…In addition, peripheral populations, which were colonized more recently, exhibited lower levels of genetic diversity compared to those central to the species' distribution. Isolation by distance was weaker in these peripheral populations, indicating that historical colonization effects continue to mask the influence of current dispersal in these populations (Costello et al 2003). Using canonical correspondence analysis (CCA) to relate various environmental factors to genetic variability, Angers et al (1999) found that altitude contributed significantly to population genetic differentiation in brook charr.…”
Section: H I S T O R I C a L F A C T O R S An D C O N N E C T I V I T Ymentioning
confidence: 99%
“…Attempts to use measures of habitat quality to predict current genetic variation in wild populations are in their infancy. Thus far, they rarely appear to be able to explain the partitioning of diversity in natural populations (Angers et al 1999;Costello et al 2003). This might reflect our incomplete understanding of the complex nature of the relationship between habitat quality and population dynamics.…”
Section: Demographic and Ecological Correlates Of Genetic Variabilitymentioning
confidence: 99%